DECISION SUPPORT SYSTEM FOR SELECTING THE BEST MASTER PULSE DEALER TO DETERMINE MONTHLY BONUSES USING THE SIMPLE ADDITIVE WEIGHTING METHOD - Yuwono, Bagus Prastowo; Fernando, Yusra (Jurnal Teknik Informatika (Jutif), 2024)
The pulse industry is one of the most dynamic and competitive business sectors, selecting the right master dealer is critical to ensuring optimal business performance. However, a manual selection process can be cumbersome. In this context, user of a decision support system (SPK) that uses simple additive weighting (SAW) are essential. This research aims to design and implement the SPK o.’[uj This research aims to design and implement a system that allows pulse business owners to select the best master dealer more efficiently and objectively. The SAW method is used to calculate the relative weight of each criterion used in the selection of master dealers, such as total transactions, total deposits, number of agents and product marketing. The use of this method makes it possible to assign a relative value to each criterion, according to the preferences and interests of the business owner. By using this SPK, they can determine the master dealer that best suits their business needs and maximize the monthly bonus earned. In addition, the integration of technology in the selection process can also improve operational efficiency and reduce human errors that may occur in manual processes. And in the ranking stage, the final result of the master dealer has been selected on behalf of Ilmi with the highest score of 1.0 and Gagah with the lowest score of 0.26.